2015
DOI: 10.1016/j.vaccine.2015.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Invasive disease potential of pneumococci before and after the 13-valent pneumococcal conjugate vaccine implementation in children

Abstract: In children <2 years old, compared to the previous period, the number of serotypes having a high disease potential decreased after PCV13 implementation, only two non-vaccine serotypes, 24F and 12F, had high invasive disease potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
57
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 38 publications
7
57
0
1
Order By: Relevance
“…Our analysis of serotype distributions demonstrated that 12F, 24F, 23B and 10A were the most frequent non-vaccine serotypes that emerged in the entire French population during the post-PCV13 period. Serotype 12F reached the dominant position in 2011–2013 for the entire population and for children under 5 years old, thereby confirming earlier findings in France [33, 34] and other countries reporting its outbreak or hyperinvasivity [3538]; its highly invasive disease potential was also recently shown in France for children under 2 years old [39]. With the same elevated invasive disease potential as 12F, we reported serotype 24F emergence in France [39], as in many other European countries [6, 40].…”
Section: Discussionsupporting
confidence: 85%
“…Our analysis of serotype distributions demonstrated that 12F, 24F, 23B and 10A were the most frequent non-vaccine serotypes that emerged in the entire French population during the post-PCV13 period. Serotype 12F reached the dominant position in 2011–2013 for the entire population and for children under 5 years old, thereby confirming earlier findings in France [33, 34] and other countries reporting its outbreak or hyperinvasivity [3538]; its highly invasive disease potential was also recently shown in France for children under 2 years old [39]. With the same elevated invasive disease potential as 12F, we reported serotype 24F emergence in France [39], as in many other European countries [6, 40].…”
Section: Discussionsupporting
confidence: 85%
“…1 Currently, more than 94 different pneumococcal serotypes have been identified and are classified on the basis of unique polysaccharides expressed in the capsule. 2 In 1983, a 23-valent pneumococcal polysaccharide vaccine (PPV23) was indicated for pediatric populations at high risk for pneumococcal disease and for older adults. In 2000, a pneumococcal conjugate vaccine (PCV) which included serotypes 4, 6B, 9V, 14, 18C, 19F and 23F (7-valent; PCV7) was first licensed in the USA and indicated for the prevention of pneumococcal disease in pediatric populations.…”
Section: Introductionmentioning
confidence: 99%
“…4 Furthermore, while the implementation of PCVs has resulted in a substantial reduction of the incidence of IPD related to the decrease in vaccine-type (VT) IPD, there has been an observed increase in non-VT IPD. 2 This highlights the need to monitor serotype data after pneumococcal vaccines (i.e., PCV10, PCV13) are adopted in different countries to observe changes in serotype prevalence and identify newly emerging serotypes. During recent years, after adoption of PCV13 in both pediatric and adult populations in multiple countries, an increasing number of studies from around the world have been conducted, which demonstrate the changing patterns of pneumococcal serotype distributions.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, significant invasive indices for IPD were identified with vaccine serotypes 4, 14, and 18C (present in PCV7 and PCV13) and 1, 5, 7F, and 19A (present in PCV13). 3 A decrease in the incidence of IPD has been reported in all the countries in which PCVs have been introduced. A reduction in IPD has been attributed to the reduction in vaccine-type IPD.…”
Section: Introductionmentioning
confidence: 99%
“…Only six serotypes, 24F, 19A, 12F, 15B/C, 10A, and 15A, represented 60.7% of IPD cases. 3 In the Turkish pneumococcal disease surveillance system, the proportion of non-vaccine serotypes was stated to be 27% in the 2008-2011 period and 38% in 2011-2014 period. There was a significant reduction (20%) in the number of isolates in the latter period, possibly owing to the impact of the national pediatric vaccination program which included PCVs, 6,7 Two of the patients in the current study who had completed the age-appropriate PCV13 vaccine series acquired serotype 19F, indicative of a vaccine breakthrough.…”
Section: Introductionmentioning
confidence: 99%